2004
DOI: 10.1002/gepi.10316
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Bayes model for random haplotype and family effects in the transmission of fragile‐X

Abstract: A model for the transmission of the CGG repeat sequence associated with the fragile-X dynamic mutation in the FMR1 gene is developed. The model incorporates both haplotype and family effects on the expansion rate of the sequence. The resulting random effects model is fitted to new data, using computer-intensive Markov chain Monte Carlo methods. The results demonstrate both the FRAXAC1-DXS458 haplotype and family effects on the transmission of CGG repeats from mother to offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The major modifying factor is the sex of a parent, where, as described above, the risk of expansion of PM alleles is limited to the mothers but for the GZ alleles, it is relatively higher for the fathers than from the mothers. 89 In addition, the data from large pedigrees suggested that the sex of offspring might be another modifying factor, with male offspring manifesting higher rate of large expansions from the parent than female offspring; 91,92 however this concept still remains controversial. 78,93 …”
Section: Small Cgg Expansion Alleles As the Source Of The Full Mutatimentioning
confidence: 99%
“…The major modifying factor is the sex of a parent, where, as described above, the risk of expansion of PM alleles is limited to the mothers but for the GZ alleles, it is relatively higher for the fathers than from the mothers. 89 In addition, the data from large pedigrees suggested that the sex of offspring might be another modifying factor, with male offspring manifesting higher rate of large expansions from the parent than female offspring; 91,92 however this concept still remains controversial. 78,93 …”
Section: Small Cgg Expansion Alleles As the Source Of The Full Mutatimentioning
confidence: 99%